An Insight into the Potential Mechanism of Bioactive Phytocompounds in the Wound Management - Khaire, Manisha; Bigoniya, Jagriti; Bigoniya, Papiya (Pharmacognosy Reviews)
Skin plays a fundamental role in the protection against mechanical impacts and infections, fluid imbalance, variations in temperature, micro-organisms, radiation, and chemical injury. Wounds are any damage or injury that disturbs the normal structure and function of the skin tissue. Wound healing is a crucial physiological process to maintain the integrity of the skin following injury by tissue repair, regeneration, and remodelling. Routinely, wound healing is a rapid and uncomplicated process, though wounds associated with impairment in host functionality are hard to heal due to diabetes, oxidative stress, chronic infection, immunosuppression, or obesity. Chronic wounds affect millions of patients physically and mentally, drastically reducing their quality of life. Therefore, new treatment strategies are urgently needed. Phytoconstituents are components derived from plants that have been used to treat wounds over the years. Various scientists have reported the crucial role of bioactive phytochemicals in wound healing and promoting skin regeneration. Numerous phytochemical compounds isolated from medicinal plants have been reported to scavenge free radicals, fight infection, and promote faster wound healing. This article aims to review the role of phytochemicals as wound healing agents with a current understanding of mechanisms, molecular targets, and therapeutic efficacy in enhancing wound repair and skin regeneration. Extensive preclinical research and clinical trials are required to understand the mechanism and potential molecular targets responsible for the beneficial impact of phytochemicals in wound healing and skin regeneration.
Keywords: Wound healing; Phytoconstituents; Antioxidant; Antimicrobial; Angiogenesis; Growth factor